DEK:AFF2 Fusion Carcinomas of Head and Neck. (12th March 2023) - Ruangritchankul, Komkrit; Sandison, Ann
Abstract : A novel DEK::AFF2 fusion carcinoma was recently described in 29 patients who originally presented with non-viral–associated nonkeratinizing squamous cell carcinoma. The tumors occurred at multiple sites in the head and neck including in the sinonasal tract, middle ear, and temporal bone. This tumor behaves aggressively involving adjacent vital structures, frequently recurs, and is inclined to develop lymph node and distant metastasis. This review aims to summarize the demographic, clinical, pathologic, immunophenotypic features, and pattern of molecular alterations as well as to discuss the differential diagnosis of DEK::AFF2 fusion carcinoma.